Estimation of fracture size and azimuth in the universal elliptical disc model based on trace information - Jichao Guo; Jun Zheng; Qing Lü; Jianhui Deng (Journal of Rock Mechanics and Geotechnical Engineering, 2023)
The geometric characteristics of fractures within a rock mass can be inferred by the data sampling from boreholes or exposed surfaces. Recently, the universal elliptical disc (UED) model was developed to represent natural fractures, where the fracture is assumed to be an elliptical disc and the fracture orientation, rotation angle, length of the long axis and ratio of short-long axis lengths are considered as variables. This paper aims to estimate the fracture size- and azimuth-related parameters in the UED model based on the trace information from sampling windows. The stereological relationship between the trace length, size- and azimuth-related parameters of the UED model was established, and the formulae of the mean value and standard deviation of trace length were proposed. The proposed formulae were validated via the Monte Carlo simulations with less than 5% of error rate between the calculated and true values. With respect to the estimation of the size- and azimuth-related parameters using the trace length, an optimization method was developed based on the pre-assumed size and azimuth distribution forms. A hypothetical case study was designed to illustrate and verify the parameter estimation method, where three combinations of the sampling windows were used to estimate the parameters, and the results showed that the estimated values could agree well with the true values. Furthermore, a hypothetical three-dimensional (3D) elliptical fracture network was constructed, and the circular disc, non-UED and UED models were used to represent it. The simulated trace information from different models was compared, and the results clearly illustrated the superiority of the proposed UED model over the existing circular disc and non-UED models.